THE EFFECT OF USING THE QUESTION AND ANSWER METHOD ON THE QUESTIONING SKILLS OF FIFTH GRADE STUDENTS OF SD INPRES TAPPANJENG, BANTAENG SUB-DISTRICT. BANTAENG DISTRICT. - Serli, Serli; Rahmapatta, Rahmawati Patta (International Journal of Elementary School Teacher, 2024)
This research was motivated by the lack of questioning skills of fifth grade students at SD Inpres Tappanjeng, Bantaeng Regency. The purpose of this research is to determine the description of the use of the question and answer method, to determine the description of questioning skills, and to determine the influence of the use of the question and answer method on students' questioning skills in class V of SD Inpres Tappanjeng Bantaeng. The subjects of this research were teachers and students of classes VA and VB at SD Inpres Tappanjeng, Bantaeng Regency, totaling 17 students, consisting of 7 boys and 10 girls. The data collection techniques used are observation and documentation. The data analysis technique used was a purposive sampling approach. The results of the study showed that the question and answer method had a positive impact on students' questioning skills. Students show more active involvement in the learning process, better critical thinking in asking and making questions, students will collect questions about material they don't understand, exchange thoughts and opinions on the questions asked so that the teacher finally collects the questions and answers them. as a unit of teaching material. The impact of implementing the question and answer method on questioning skills increases in each cycle. The findings of this research provide implications for educators and in the development of more effective learning methods. From the research results, it can be concluded that the influence of the question and answer method can improve students' questioning skills in class V of SD Inpres Tappanjeng, Bantaeng Regency.